A RETROSPECTIVE CROSS-SECTIONAL ANALYSIS ON CHANGING WORK PATTERNS OF CONSULTANT ANAESTHETISTS DURING THE FIRST AND SECOND WAVES OF SARS-COV-2: IMPLICATIONS FOR FUTURE PANDEMIC PLANNING. - Malleck-Amode-Peerzada, Gunseli; Bechan, Sudha; Asmal, Imraan (Student’s Journal of Health Research Africa, 2023)
Background: The SARS-CoV-2 pandemic has significantly impacted healthcare systems, altering the work patterns of healthcare professionals. This study investigates the evolving work patterns of consultant anaesthetists at a quaternary hospital during the pandemic and examines their implications for future pandemic preparedness. Methods: The study involved a retrospective analysis of consultant working sessions between January 2019 and March 2021, extracted from the departmental schedule. These sessions were classified into three primary categories: Clinical sessions, Administrative/academic sessions, and Leave sessions, each further subdivided. Quantitative data was portrayed through counts, percentages, and ranges. A comparison was drawn between the pre-pandemic and pandemic datasets, evaluated using Mann-Whitney testing. Results: A total of 7812 work sessions were analysed Despite a reduction in total sessions during the pandemic, there was a significant shift in consultants’ allocation towards clinical sessions compared to the pre- pandemic phase (p=0.049). Allocation to "in theatre" clinical sessions displayed no significant variation (p=0.768). The increased clinical sessions during the pandemic were attributed to consultants being redeployed to Cut-off theatre clinical roles, such as the COVID ICU and COVID team. No significant increase was seen in sick leave taken during the study period, however annual leave did reduce significantly. Academic sessions also experienced a significant drop in sessions. Conclusion: The study reveals shifts in the work patterns of anaesthetic consultants in response to the global health pandemic. Clinical sessions increased within the anaesthetic department due to staff redistribution to out-of-theatre COVID-related responsibilities. The findings emphasize the importance of effective workforce planning and crisis management strategies to ensure continuous essential healthcare delivery by anaesthetists during future pandemics. Recommendation: Adaptable workforce planning, staff flexibility, novel roles, and revised session structures, is pivotal in addressing pandemic challenges and meeting unique demands effectively.